Study on an application of bioengineering by layer TIRF measurement - Syukran Hakim, Norazman (2013)
The nature inside bacterial cell has traditionally been viewed as an environment where intermolecular interactions are governed by isotropic diffusion. However, in latest studies, it is reported that the interactions are sub-diffusive. In order to have better understanding on this phenomenon, it is necessary to conduct a 3-dimensional measurement of biological substance's high-speed motion at nano-scale. In recent years, measurement of biological substance has significantly advanced since the introduction of TI RFM (Total Internal Reflection Fluorescence Microscopy). TI RFM uses evanescent light to illuminate and capture images from samples located a few hundred nano-metersfrom the microscope glass plate. Originally, TIRFM can only be used to measure samples in 2-dimensional. However, a method to image samples in pseudo 3-dimensional, called layer TIRF has been developed. In this method, it is possible to calculate the pseudo z-coordinate by matching the decaying ratio of evanescent light to the particle's z-axis location. Up until now, only low-speed measurement has been made. In this work, a high speed measurement was achieved. First, calibration of static particles were conducted. Magnesium Fluoride (MgF 2 ) patterns with a width of 10[4m] and thickness of 100200 [nm] were fabricated onto a glass plate. Bio-nanoparticles were placed onto the plate and z-axis coordinate were calibrated. Then, 3-dimensional Brownian motion of the bionanoparticles near the glass wall were captured using a high speed EMCCD camera. A low pass filter algorithm was used to reduce noise in captured images. The diffusion coefficient of bionanoparticles were calculated and the result obtained was close to the theoretical values.